SISTEM AKUNTANSI BIAYA PADA PERUSAHAAN MANUFAKTUR - Cantika Marcelly Pardosi; Yohana Sembiring; Alfiya Husna (Sekolah Tinggi Ekonomi dan Bisnis Islam (STEBIS) Al-Ulum, 2024)
The cost accounting system is a series of procedures used to record, classify, process, and report production costs so that companies obtain accurate and relevant cost information. This paper discusses the fundamental concepts of a cost accounting system, including its objectives, functions, elements, procedural networks, and the importance of internal control within the cost-processing cycle. The discussion covers the functions involved—such as production, warehousing, accounting, and sales—as well as the documents and accounting records used, including production orders, material requisition forms, time cards, cost sheets, and product cost cards. Furthermore, the paper explains the cost-recording process starting from data collection, cost classification, cost processing using methods such as job order costing, process costing, activity-based costing, and standard costing, to the preparation of management reports. Modern aspects of cost accounting systems related to risks such as recording errors, fraud, and data loss are also discussed, along with control measures including authorization, verification, the use of technology, and system security. The implementation of a cost accounting system is illustrated through a case study of a food manufacturing company, showing the flow of costs from raw material purchases, labor usage, and overhead costs to production completion and product sales. Overall, the cost accounting system plays a critical role in supporting operational efficiency, cost control, and managerial decision-making. Keywords: Cost accounting system, production cost, internal control, accounting documents, production process, cost of production, accounting information system.